Studi Analisis Peran BAZNAS Microfinance Desa (BMD) Yogyakarta Terhadap Peningkatan Kesejahteraan Mustahik Berdasarkan Model CIBEST - Nazah, Risma Khoirun; Amri, Muhtadin (Institut Agama Islam Negeri Ponorogo, 2022)
Risma Khoirun Nazah1*, Muntadin Amri2 1 Instutut Agama Islam (IAIN) Ponorogo, Indonesia, iain.po.ac.id2 Institut Agama Islam Negeri Ponorogo, Indonesia3 khoirunnajah99@gmail.comAbstract: Capital is one of the problems that often hinders the movement of people's businesses, especially in the midst of this Covid-19 pandemic situation. Capital problems are also one of the triggers that lead to the emergence of poverty problems. Therefore, with the presence of the BAZNAS Microfinance Village (BMD) Yogyakarta institution, it is hoped that it will be able to overcome capital problems while improving the welfare of the community. The purpose of this study was to analyze the form of productive zakat empowerment in the BAZNAS Microfinance Village (BMD) Yogyakarta program. To analyze the empowerment strategy of BAZNAS Microfinance Village (BMD) Yogyakarta in improving the welfare of mustahik. To analyze the implications or impact of the Yogyakarta BAZNAS Microfinance Village (BMD) program on improving the welfare of mustahik based on the CIBEST model. This research method uses a descriptive qualitative approach, primary and secondary data sources with a population of 80 mustahik of BMD Yogyakarta's fostered partners, where the total sample of respondents is 17 mustahik consisting of 8 mustahik of TBS Honey, 4 mustahik of Grogol SMEs, and 5 mustahik of Mitra Sejahtera Livestock Group. (KTMS). The data processing and analysis technique in this research is using the CIBEST Model index. The results of the study using the CIBEST measurement analysis method found that the poverty level of mustahik recipients of capital loan assistance from the Yogyakarta BAZNAS Microfinance Village (BMD) program decreased, so that the welfare level of mustahik increased. Based on the calculation of the CIBEST model before the Yogyakarta BMD program, it was found that the welfare index was 0.29, the material poverty index was 0.58, the spiritual poverty index was 0, and the absolute poverty index was 0.11. After the Yogyakarta BMD program, each of these indexes underwent changes, first the welfare index increased by 18% to 0.47. The material poverty index decreased by 17% to 0.41, the spiritual poverty index increased by 5% to 0.05 and finally the absolute poverty index decreased by 6% to 0.05.Keywords: BAZNAS Microfinance Desa (BMD), welfare, CIBEST Model. Abstrak: Permodalan merupakan salah satu permasalahan yang kerap menghambat gerak usaha masyarakat apalagi ditengah situasi pandemi Covid-19 ini. permasalahan permodalan juga menjadi salah satu trigger yang mengakibatkan munculnya permasalahan kemiskinan. Karenanya dengan hadirnya lembaga BAZNAS Microfinance Desa (BMD) Yogyakarta diharapkan mampu mengatasi permasalahan permodalan sekaligus meningkatkan kesejahteraan masyarakat. Tujuan penelitian ini adalah untuk menganalisis bentuk pemberdayaan zakat produktif pada program BAZNAS Microfinance Desa (BMD) Yogyakarta. Untuk menganalisis strategi pemberdayaan BAZNAS Microfinance Desa (BMD) Yogyakarta dalam meningkatkan kesejahteraan mustahik. Untuk menganalisis implikasi atau dampak program BAZNAS Microfinance Desa (BMD) Yogyakarta terhadap peningkatan kesejahteraan mustahik berdasarkan model CIBEST. Metode penelitian ini menggunakan pendekatan kualitatif deskriptif, sumber data primer dan sekunder dengan jumlah populasi 80 mustahik mitra binaan BMD Yogyakarta, dimana jumlah sampel responden sebanyak 17 mustahik yang terdiri dari 8 mustahik Madu TBS, 4 mustahik UMKM Grogol, serta 5 mustahik Kelompok Ternak Mitra Sejahtera (KTMS). Teknik pengolahan dan analisis data dalam penelitian ini adalah dengan menggunakan indeks CIBEST Model. Hasil penelitian menggunakan metode analisis pengukuran CIBEST ditemukan bahwa tingkat kemiskinan mustahik penerima bantuan pinjaman modal program BAZNAS Microfinance Desa (BMD) Yogyakarta mengalami penurunan, sehingga tingkat kesejahteraan mustahik meningkat. Berdasarkan penghitungan CIBEST model sebelum adanya program BMD Yogyakarta diperoleh bahwa indeks kesejahteraan sebesar 0.29, indeks kemiskinan material sebesar 0.58, indeks kemiskinan spiritual sebesar 0, dan indeks kemiskinan absolut sebesar 0.11. Setelah adanya program BMD Yogyakarta masing-masing indeks tersebut mengalami perubahan, pertama indeks kesejahteraan mengalami peningkatan sebesar 18% menjadi 0.47. Indeks kemiskinan material mengalami penurunan sebesar 17% menjadi 0.41, pada indeks kemiskinan spiritual mengalami peningkatan sebesar 5% menjadi 0.05 dan terakhir pada indeks kemiskinan absolut mengalami penurunan sebesar 6% menjadi 0.05. Kata kunci: BAZNAS Microfinance Desa (BMD), Kesejahteraan, CIBEST Model.